People of the Volcano : Andean Counterpoint in the Colca Valley of Peru - Cook, Noble David; Cook, Alexandra Parma (Book collections on Project MUSE., 2007)
First full-length history of the Colca Valley in southern Peru from pre-Hispanic times to the present.